Venire senza provenire: il diritto di accesso dell’adottato alle proprie origini nelle strettoie dell’anonimato materno (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article analyses the judicial path, crossed by lights and shadows, and its ability to make it feasible to more easily learn information about one’s own parental history in anonymous birth. A comparison is made between the European Court of Human Rights (ECtHR) case law and the Italian Constitutional Court case law, showing differences in the methods but strong similarities in the substantive solutions. Conclusively, in the Italian legal system, the mother’s decision to confirm her original choice for anonymity has an undisputed prevalence when it tries to balance with the child’s constitutional right to have his or her own personal experience recognised.
Keywords: Anonymous birth; right to know one's origins; right to respect for private life